Non-Pharmacological Therapies to Reduce Anxiety Levels of Pregnant Women & Maternity Mothers: A Systematic Literature Review - Fauziah Yulfitria (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
A common mental health problem affecting millions of women all around is anxiety before pregnancy and after delivery. Untreated, it might cause early deliveries, reduced birth weights, bad infant bonding, and children's long-term developmental difficulties. Many mothers choose natural cures than from drugs for safety worries relating to their children. Recent research on non-drug approaches to lessen anxiety in pregnant women and new mothers is examined in this review. Focusing on multiple non-drug treatments, a comprehensive search was conducted in PubMed and Google Scholar. The results indicate that yoga and mindfulness-based stress reduction measures practically reduce anxiety. For treating anxiety, non-drug treatments are safe choices that healthcare professionals should integrate into maternal care. More research is needed for consistent methods and long-term studies to support clinical practices.